Are Zooxanthellae Really Sensitive? Response of Zooxanthellae Size Exposed to Several Pollutants - Ambariyanto Ambariyanto; Diah Permata Wijayanti; Munasik Munasik; Puji Eka Purnama; Mu’alimah Hudatwi; Ni Made Ernawati; Alferd Y. Ko'ou (Marine Science Department Diponegoro University, 2018)
Pollution is one of the important issues faced by marine resources including zooxanthellae, which is known to be very sensitive to environmental changes. Some pollutants have been reported to have adverse effects on zooxanthellae, however, their sensitivity in regards to changes on cell size of these algae has not been widely explored. This study examined the effects of pollutants on the sensitivity of zooxanthellae through changes in size. Zooxanthellae were isolated from corals Porites lutea, Acropora aspera, and Montipora digitata collected from Panjang Island, Jepara, Indonesia. These algae were exposed to pollutants i.e. heavy metals (Cu, Cd, Pb) and nutrients (ammonium and phosphate) at concentrations of 5,10,15 ppb and 5,10,15 μM, respectively. Zooxanthellae size were measured five hours after pollutants exposure. The results showed that all treatments reduced the size of zooxanthellae. Algae isolated from P. lutea are the least affected by pollutants and the highest percentage cell size reduction was found in phosphate treatment. However, reduction on the size of algae were not statistically significant. These results indicate that in relation to reduction in the size, zooxanthellae are not sensitive to pollutants. Keywords: Zooxanthellae, pollutants, sensitivity, size reduction